Perbedaan Pengaruh Model Pembelajaran PjBL dan PBL dalam Peningkatan Keterampilan Pengukuran Siswa SMK: Penelitian - Wahyu Adi Wijaya; Marsono (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research aims to identify the most effective teaching method between Problem-Based Learning (PBL) and Project-Based Learning (PJBL) for enhancing vocational high school students' measurement skills on the topic of measuring instruments. Measurement is a fundamental competency highly needed by Vocational High School students, especially in technical fields. The research applied a quasi-experimental design that incorporated a pretest-posttest control group model. The research sample consisted of Vocational High School students divided into two groups, one group of Vocational High School students implemented the PBL method, while the other group used PJBL. The researcher collected data through practical skills tests and attitude questionnaires, as well as observation sheets, which were then analyzed using descriptive and inferential techniques via paired sample t-tests and correlation analysis. Research findings demonstrate that students show better measurement skills improvement when taught using the PJBL method compared to the PBL approach. Students who used the PJBL method showed an increase in skills in using measuring instruments and measurement accuracy, as well as team collaboration during project implementation. PJBL's project-based structure encourages students to become more active participants while directly applying concepts. Educators should incorporate PJBL in teaching measurement material based on the data from this research. Further in-depth studies can provide insights into the long-term effects of PJBL on various additional technical skills.